Comparison of HASTE versus EPI-Based DWI for Retinoblastoma and Correlation with Prognostic Histopathologic Parameters - Sharma, Manish; Gupta, Amit; Jana, Manisha; Kashyap, Seema; Bakhshi, Sameer; Sharma, Sanjay (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Non-EPI-based DWI has shown better performance in head and neck pathologies owing to lesser susceptibility artifacts compared with EPI-DWI. However, only sporadic studies have investigated the feasibility of non–EPI-based DWI in retinoblastoma (RB). We qualitatively and quantitively compared EPI-DWI and HASTE-DWI in RB and correlated the tumor ADC values obtained from these 2 techniques with histopathologic markers.MATERIALS AND METHODS: Twenty-one treatment-naive patients with RB underwent 1.5T orbital MR imaging. EPI-DWI and HASTE-DWI were acquired at 3 b-values (0, 500, and 1000 s/mm2). All patients subsequently underwent surgical enucleation. For qualitative image assessment, scoring of overall image quality, artifacts, tumor sharpness, and tumor conspicuity was done by using a 5-point Likert scale. Quantitative assessment included calculations of SNR, contrast-to-noise ratio (CNR), geometric distortion, and ADC. Qualitative scores were compared by using the Wilcoxon signed-rank test, and quantitative parameters were analyzed with a t test.RESULTS: All 21 patients had unilateral RB; 15 were male and 6 were female with a median age of 36 months (range, 9–72 months). On histopathology, patients had either poorly differentiated (n = 13/21) or moderately differentiated (n = 8/21) RB. Other poor prognostic markers evaluated were optic nerve invasion (n = 10/21), choroidal invasion (n = 12/21), and anterior eye segment enhancement on MRI (n = 6/21). HASTE-DWI demonstrated higher image quality scores than EPI-DWI (P < .01), except for tumor conspicuity score, which was higher for EPI-DWI (P < .001). HASTE-DWI showed lower SNR, CNR, and geometric distortion than EPI-DWI (P < .001). The average acquisition times of EPI-DWI and HASTE-DWI were ~1 and 14 minutes, respectively. The mean tumor ADC value on EPI-DWI was 0.62 extpm 0.14 exttimes 10-3 mm2/s and on HASTE-DWI was 0.83 extpm 0.17 exttimes 10-3 mm2/s. A significant correlation between EPI-DWI and HASTE-DWI ADC values (r = 0.8; P = .01) was found. Lower ADC values were found in tumors with poor prognostic markers, but none reached a statistically significant difference.CONCLUSIONS: HASTE-DWI shows improved overall image quality; however, it lacks in terms of tumor conspicuity, SNR, CNR, and longer acquisition time compared with EPI-DWI. ADC values derived from HASTE-DWI show no advantage over EPI-DWI in correlation with histopathologic prognostic markers.CNRcontrast-to-noise ratioEPI-DWIEPI-based DWIRBretinoblastoma